Reactive Power Management of Power Networks with Wind Generation - Amaris, Hortensia. (Lecture Notes in Energy, 2013)
As the energy sector shifts and changes to focus on renewable technologies, the optimization of wind power becomes a key practical issue. Reactive Power Management of Power Networks with Wind Generation brings into focus the development and application of advanced optimization techniques to the study, characterization, and assessment of voltage stability in power systems. Recent advances on reactive power management are reviewed with particular emphasis on the analysis and control of wind energy conversion systems and FACTS devices.   Following an introduction, distinct chapters cover the 5 key areas of FACTS devices, voltage stability, wind generators, reactive power optimization and management. These are supported with applications and example including real-life data from the Spanish Power system.   Together with power system engineers, operators and planners will also benefit from this insightful resource. Reactive Power Management of Power Networks with Wind Generation provides a key reference to advanced undergraduate and graduate students in electrical and power engineering.